The effect of special exercises for some physical, motor and electrical abilities accompanied by symmetrical electrical stimulation in the rehabilitation of the muscles of the arms of patients with simple hemiplegic cerebral palsy - jawad kadhim, Mohameed; Mahmood, Hasnaa (Journal of Physical Education, 2023)
The aim of the research is to know the effect of using special exercises for some physical, motor and electrical abilities, accompanied by symmetrical electrical stimulation, in rehabilitating the muscles of the arms for patients with simple hemiplegic cerebral palsy. In favor of the simple test and the post test, the researchers used the experimental approach (one group design with two pre and post tests) due to its suitability to the nature of the problem to be solved. As for the research community, it was represented by people with simple hemiplegic cerebral palsy, whose ages ranged from (35 years and over), while the research sample consisted of (5) people with simple hemiplegia of the right arm and right leg. The researchers concluded that the early rehabilitative approach is more useful in rehabilitating the muscles that do not reach the induction, and that the use of symmetrical electrical stimulation is better than the use of external stimulation whose intensity is not controlled. The need to unify the rehabilitation curricula in the Iraqi Ministry of Health and rehabilitation centers, to develop diagnostic tests to know the onset of paraplegia and tests to diagnose complete rehabilitation